Respostas ecofisiológicas de Dipteryx alata Vogel em diferentes níveis de radiação solar - Borella, Daniela Roberta (2018)
The objective of this study was to identify the ecophysiological responses of Dipteryx alata Vogel seedlings at increasing shading levels (black polyester screens) and spectral solar radiation (colored polyester screens) and in full sun during the dry season of the Central-North region of Mato Grosso State. The experiment was conducted between June and October 2017 in a randomized complete block design, with four replications consisting of nine seedlings. Non-destructive growth and photosynthesis analyzes were performed fortnightly and destructively at 125 DAT, with counting the number of leaves and leaflets and measuring the height, diameter, photosynthetic rate, stomatal conductance, transpiration and foliar temperature, and the second , obtaining the dry mass of the leaves, stem and root; leaf area; length and root volume. The ETc was obtained by capillary lysimeters and reference evapotranspiration (ET0) by the Penman-Montheit Fao 56 method, with values Kc defined by the ETc and ET0 ratio. The mean daily air temperature in the full sun, black screen and thermoprofile was 26.0 ± 0.2 ° C and in the red, blue and green screens were 26.64; 26.84 and 26.72 ° C, respectively. The average daily relative humidity of the air in the full sun condition was 55.79%, in the black screen of 83.3% it was 61.31% and in the other screens 60.00% of humidity. The total daily global solar radiation decreased as the shading level increased, with the greatest oscillation in the range of 10.18 to 24.96 MJ m-2d-1 in the full sun condition. The different levels of shading and spectra of solar radiation did not affect the growth of the D. alata seedlings, however, it increased the leaf area with the increase of the level of shading, with extreme values in full sun (93.02 cm²) and in the screen of 83,3% (243,61 cm²), in the spectral levels of HG the extreme values were in the screens blue (77,04 cm²) and green (187,66 cm²). The photosynthetic rate, stomatal conductance and transpiration of the seedlings were influenced by microclimatic dynamics during the dry season. The ETc of the D. alata seedlings and its Kc increased with the highest incidence of solar radiation in the shading screens, 4.34 mm dia-1 and 1.23 in the full sun condition at 3.54 mm dia-1 and 0, 99 in the screen 83.3% of shading, in the colored there was increase in the order of: blue screen (3.05 mm dia-1 and 0,87), red (3,08 mm day-1 and 0,88), thermo-reflecting (3.27 mm dia-1 and 0.92) and green (3.48 mm dia-1 and 0.99). The production of D. alata seedlings depends on the cost-benefit ratio of the shades screens and the local water availability, when water is not a limiting factor, it is recommended to produce in full sun.